Critical Issues for the Tomato Industry: Preventing a Rapid Postharvest Breakdown of the Fruit - Jerry A. Bartz; Steven A. Sargent; Phyllis R. Gilreath (EDIS)
HS-1107, a 6-page illustrated guide by J. A. Bartz, S. A. Sargent, and P. R. Gilreath, provides a history of the problem, key symptoms and causes for the two postharvest diseases that normally cause it, and a quick checklist of suggestions for minimizing rapid breakdown of tomato fruit. Includes references. Published by the UF Department of Horticultural Sciences, July 2007.